2007
DOI: 10.1007/s12098-007-0064-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of Kamar tribal children in Chhattisgarh

Abstract: Undernutrition in the form of underweight, stunting and wasting and low consumption of dietary intake (energy and protein) was found to be widely prevalent among Kamar tribal children. Therefore, an urgent dietary intervention programme is necessary. Further studies are required to investigate into problem and to supplement the key nutrients which are required to ensure a good nutritional status in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 8 publications
2
25
1
Order By: Relevance
“…For the Mishmi children, we found a significantly lower stunting rate at 11.6%. The prevalence of stunting was found to be less prevalent than the 50% reported for the Kamar children of Chhattisgarh [11], 54% for the Oraon of North Bengal [12], the 54% reported in the tribal children of Bihar [20], and the 45.8% found in children of West Bengal [27]. The present study found the incidence of underweight children to be 23.3% which distinctly lower than 61.1% found among tribal children of Madhya Pradesh [21] and the 60% found among children from Rajasthan [25].…”
Section: Discussioncontrasting
confidence: 58%
“…For the Mishmi children, we found a significantly lower stunting rate at 11.6%. The prevalence of stunting was found to be less prevalent than the 50% reported for the Kamar children of Chhattisgarh [11], 54% for the Oraon of North Bengal [12], the 54% reported in the tribal children of Bihar [20], and the 45.8% found in children of West Bengal [27]. The present study found the incidence of underweight children to be 23.3% which distinctly lower than 61.1% found among tribal children of Madhya Pradesh [21] and the 60% found among children from Rajasthan [25].…”
Section: Discussioncontrasting
confidence: 58%
“…But it was higher in the present study than in tribal preschool children of Baiga, [22] Kodaku, [23] Raj Gond [24] and Lodha. [25] In contrast, the prevalence of stunting was lower in the present study than in the Saharias, [26] Kamars [27] and tribal children from Bihar, [28] Maharastra [29] and West Bengal. [20] However, the rate of stunting was similar to that of the national tribal population, and higher than that of the other national population (40.7%).…”
Section: Discussionmentioning
confidence: 58%
“…Many studies across the country have been conducted to know the nutritional status of under five children and also among various tribal communities [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%